2021
DOI: 10.1029/2020gl090903
|View full text |Cite
|
Sign up to set email alerts
|

Changing Spatial Structure of Summer Heavy Rainfall, Using Convection‐Permitting Ensemble

Abstract: Subdaily rainfall extremes have been found to intensify, both from observations and climate model simulations, but much uncertainty remains regarding future changes in the spatial structure of rainfall events. Here, future changes in the characteristics of heavy summer rainfall are analyzed by using two sets (1980–2000, 2060–2080) of 12‐member 20‐year‐long convection‐permitting ensemble simulations (2.2 km, hourly) over the UK. We investigated how the peak intensity, spatial coverage and the speed of rainfall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…Our results, which pertain to daily precipitation, assume no change in the spatial structure of precipitation events at scales smaller than the resolutions of the used climate models. Improvements in the statistical description of the precipitating systems at multiple temporal and spatial scales derived from observations and/or convection‐permitting models could fill this gap by quantifying their structural response to external forcing (Cannon & Innocenti, 2019; Chen et al., 2020; Marra, Borga, et al., 2020; Peleg et al., 2018; Wasko et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our results, which pertain to daily precipitation, assume no change in the spatial structure of precipitation events at scales smaller than the resolutions of the used climate models. Improvements in the statistical description of the precipitating systems at multiple temporal and spatial scales derived from observations and/or convection‐permitting models could fill this gap by quantifying their structural response to external forcing (Cannon & Innocenti, 2019; Chen et al., 2020; Marra, Borga, et al., 2020; Peleg et al., 2018; Wasko et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Both studies showed that total rain area and the convective core area scale with temperature in opposite directions: total area exhibits a negative scaling, while the area of the convective cores is positively scaled with temperature; this is probably related to an enhanced moisture convergence into the convective cores from the total storm extent. In contrast, results from studies of future extreme precipitation in the Netherlands and in the UK show the area of the storms is expected to increase with global warming (Y. Chen, Paschalis, et al., 2020; Lochbihler et al., 2017, 2019), which may indicate a regional dependence in the scaling of the rain area, but this topic should be addressed in future studies (Fowler, Lenderink, et al., 2021).…”
Section: Summary and Discussionmentioning
confidence: 94%
“…Future rainstorms simulated in this work show quite a difference in rainfall patterns compared to historic rainstorms, mainly being more concentrated in both space and time. Given that the conditional rain rate increases, one might expect an increase in total precipitation during HPEs, as projected, for example, over Europe (e.g., Y. Chen, Paschalis, et al., 2020; Hawcroft et al., 2018; Kendon et al., 2014). However, two other factors, less often addressed, negatively affect total rainfall: the size of the rain area, and the duration of the events.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Moreover, CPRCM projections were performed to assess the impacts of climate change on the solar resources (Carreño et al, 2020) that would consequently affect power system operations (Craig et al, 2019) and high energy stress periods in a region (Texas) with high wind and solar penetrations (Craig et al, 2020). Finally, Chen et al (2021) highlighted the conflicting surface solar radiation projections over the United States from GCMs, RCMs, and CPRCMs that are likely associated with the transient aerosol scenarios used in certain models.…”
Section: Evaluation Of Renewable Energy Resources and Wind Farm Impacts On Atmospheric Conditionsmentioning
confidence: 99%
“…The climate change signals of the different CPRCM simulations seem to converge, likely a consequence of the more realistic representation of local storm dynamics, providing a sign of increased accuracy of future changes of extreme summer precipitation. In a study covering the entire UK using a CPRCM ensemble, Chen et al (2021) projected that summer heavy rainfall will be more intense, with a faster translation speed, and a wider spatial coverage.…”
Section: Climate Change Projections Using Cprcmsmentioning
confidence: 99%